Exploring Predictive Role of Self-Esteem, Coping Behavior, and Early Maladaptive Schema in Academic Procrastination - Mustafali, Urfan; Koşucu, Deniz; Bürüce, Dilan; Tosun, Gizem Seval; Demiralp, Atacan; Dabanoğlu, Gamze; Adalı, Raif; Tunusluoğlu, Mustafa Kemal; Zajenkowska, Anna (Studia Psychologica: Theoria et praxis, 2025)
Procrastination, defined as the habitual and unnecessary delay of important tasks, appears in various contexts, including academia. It is particularly evident among students who tend to defer academic responsibilities such as exam preparation and homework completion. This study examines the predictive roles of self-esteem, emotion-focused coping, and maladaptive schemas in academic procrastination. We hypothesized that self-esteem would predict lower levels of academic procrastination and, most importantly, explored whether higher levels of emotion-focused coping and insufficient self-control schemas predict academic procrastination beyond the impact of self-esteem. An online survey was conducted with 137 (85 female, 52 male) students pursuing undergraduate, master's, and doctoral education in Poland. Only self-esteem and insufficient self-control schema emerged as significant predictors of academic procrastination while emotion-focused coping was not significant. Results can inform the design of intervention programs aimed at improving students' academic performance by addressing the emotional (self-esteem) and cognitive (self-control schema) aspects of procrastination rather than behavioral (coping).